From culture to commerce: A literature review on cross-cultural influences in sustainable global marketing - Mohd Ali, Nor Amira; Abdul Gafar , Muhammad Hanif (International Journal of Accounting, Finance and Business, 2025)
A globalized business environment creates the need for sustainable marketing strategies considering cultural differences. However, there remains a gap in cross-cultural factors affecting sustainability marketing, specifically, in environmental, social, and economic dimensions. This study reviews this intersection of how sustainable global marketing is influenced by cultural dimensions. In this paper, Hofstede’s cultural dimensions and Hall’s high and low-context cultures are integrated to create a theoretical framework that explains how culture influences consumer attitudes and marketing adaptation strategies. This study draws on insights from peer-reviewed journals, books, and conference papers using a literature review approach to find out about the cross-cultural factors that shape sustainable marketing. Findings show that cultural dimensions considerably affect the consumers’ perceptions and behaviors toward sustainability initiatives. Social and environmental sustainability aspects are considered collectivist societies, while individualistic cultures emphasize economic sustainability and corporate social responsibility. This study is theoretically contributing whereby it closes the gap between cultural theories and sustainable marketing by establishing a basis from which businesses can develop their sustainability ability to satisfy needs in culturally different scenarios. Practically, it also provides insights for global marketers on how to culturally adapt sustainability initiatives, similar to businesses, and policymakers. Sustainability can be embedded in cultural narratives to improve business engagement beyond environmental preferences, thereby tapping into the cultural values and priorities of the consumer. However, there are some drawbacks, among which are dependence on secondary sources and empirical validation of the model in different markets. In the future, primary data collection on digital transformation achievement in sustainable marketing across cultures is needed. Learning about these shifting dynamics can complement global marketing strategies and the need to nurture their sustainability practices, where to adopt globally in a meaningful, not symbolic, way.